Development Education and Its Context: Between Unease and Hope - Suyapa Martínez Scott; Juan Manuel Gea Fernández; José J.Barba (Revista Electronica Interuniversitaria de Formación del Profesorado)
The concept of Development Education is analyzed in this paper. The analysis takes into account the two terms of the construct: education and development, as both and each of them are a way of approaching the reading and understanding of the World in which we live. For this reason some of the main economic theories, including the thesis of the so–called decrease, are reviewed. Next, the specific features of Development Education are taken into consideration, as well as the goals it pursues, the values it promotes and the methodology it requires, since this educational scope cannot be carried out taking any methodological approach.